Implications of marginalization and critical race theory on social justice - Chandan, Harish C. 1947- (Advances in religious and cultural studies (ARCS), 2023)
"This book takes indepth look at Critical Race Theory as an emerging transdisciplinary, race-equity methodology that originated in the 1980s legal studies and is grounded in social justice with the premise that the racism and disparate racial outcomes are the result of complex, changing and often subtle social and institutional dynamics rather than explicit and intentional prejudices on the part of individuals"--